A novel mechanism causing imbalance of mitochondrial fusion and fission in human myopathies. (19th January 2018) - Bartsakoulia, Marina; Pyle, Angela; Troncoso-Chandía, Diego; Vial-Brizzi, Josefa; Paz-Fiblas, Marysol V; Duff, Jennifer; Griffin, Helen; Boczonadi, Veronika; Lochmüller, Hanns; Kleinle, Stephanie; Chinnery, Patrick F; Grünert, Sarah; et al.
Abstract: Mitochondrial dynamics play an important role in cellular homeostasis and a variety of human diseases are linked to its dysregulated function. Here, we describe a 15-year-old boy with a novel disease caused by altered mitochondrial dynamics. The patient was the second child of consanguineous Jewish parents. He developed progressive muscle weakness and exercise intolerance at 6 years of age. His muscle biopsy revealed mitochondrial myopathy with numerous ragged red and cytochrome c oxidase (COX) negative fibers and combined respiratory chain complex I and IV deficiency. MtDNA copy number was elevated and no deletions of the mtDNA were detected in muscle DNA. Whole exome sequencing identified a homozygous nonsense mutation (p.Q92*) in the MIEF2 gene encoding the mitochondrial dynamics protein of 49 kDa (MID49). Immunoblotting revealed increased levels of proteins promoting mitochondrial fusion (MFN2, OPA1) and decreased levels of the fission protein DRP1. Fibroblasts of the patient showed elongated mitochondria, and significantly higher frequency of fusion events, mtDNA abundance and aberrant mitochondrial cristae ultrastructure, compared with controls. Thus, our data suggest that mutations in MIEF2 result in imbalanced mitochondrial dynamics and a combined respiratory chain enzyme defect in skeletal muscle, leading to mitochondrial myopathy.